Pendugaan Bobot Badan Ternak Kambing Betina Berdasarkan Ukuran Linear Tubuh di Desa Boronubaen Kecamatan Biboki Utara Kabupaten Timor Tengah Utara - Maria Yoda Haki (Program Studi Peternakan, Fakultas Pertanian, Universitas Timor, 2019)
This study aims to estimate the body weight of female goats that are traditionally raised by breeders in the village of Boronubaen, North Biboki District, North Central Timor Regency. Sampling of research and livestock is carried out by proposive sampling. The livestock that were the object of the study were 23 female goats belonging to breeders with different ages ie 1 and 2 years viewed based on fixed incisors. The method used in this study is an experimental method by making direct measurements of the linear body of a female goat and body weight. The variables measured in this study included estimating body weight, body length, chest circumference, shoulder height. The data obtained were analyzed by simple linear regression analysis according to the instructions (Akdon, 2013). The mathematical model is: Y = a + bX. Where, Y = the predicted value / projected bound variable subject; A = Constant price value; b = Regression coefficient / Direction value as a predictor / prediction showing the value of increasing (+) or decreasing value (-) of variable Y; X = free variable. It was concluded that body length at one year of age and chest circumference had a strong prediction and body weight with values ​​of 0.895 and two years of age 0.538, and chest circumference of one year of age 0.674 and two years of age of chest circumference of 0.535. 2. Shoulder height has a strong relationship between singnification and body weight of goats.